Experimental determination of efficient thermal conductivity of depth hoar - R. A. Chernov (Лëд и снег, 2015)
As a result of laboratory tests, values of the effective thermal conductivity of recrystallized snow were obtained. There are big differences between the coefficient of effective thermal conductivity of depth hoar and granular snow density in the range from 0.15 to 0.45 g/сm³. The linear dependence of the effective thermal conductivity of depth hoar on its density is given by:Kef = 0.636ρ − 0.023 W/(m °С).